Anthocyanin biosynthesis in pears is regulated by a R2R3-MYB transcription factor PyMYB10 - Feng, Shouqian; Wang, Yanling; Yang, Song; Xu, Yuting; Chen, Xuesen (Planta, 2010)
Skin color is an important factor in pear breeding programs. The degree of red coloration is determined by the content and composition of anthocyanins. In plants, many MYB transcriptional factors are involved in regulating anthocyanin biosynthesis. In this study, a R2R3-MYB transcription factor gene, PyMYB10, was isolated from Asian pear (Pyrus pyrifolia) cv. ‘Aoguan'. Sequence analysis suggested that the PyMYB10 gene was an ortholog of MdMYB10 gene, which regulates anthocyanin biosynthesis in red fleshed apple (Malus × domestica) cv. ‘Red Field'. PyMYB10 was identified at the genomic level and had three exons, with its upstream sequence containing core sequences of cis-acting regulatory elements involved in light responsiveness. Fruit bagging showed that light could induce expression of PyMYB10 and anthocyanin biosynthesis. Quantitative real-time PCR revealed that PyMYB10 was predominantly expressed in pear skins, buds, and young leaves, and the level of transcription in buds was higher than in skin and young leaves. In ripening fruits, the transcription of PyMYB10 in the skin was positively correlated with genes in the anthocyanin pathway and with anthocyanin biosynthesis. In addition, the transcription of PyMYB10 and genes of anthocyanin biosynthesis were more abundant in red-skinned pear cultivars compared to blushed cultivars. Transgenic Arabidopsis plants overexpressing PyMYB10 exhibited ectopic pigmentation in immature seeds. The study suggested that PyMYB10 plays a role in regulating anthocyanin biosynthesis and the overexpression of PyMYB10 was sufficient to induce anthocyanin accumulation.